A Major Downregulation of Circulating microRNAs in Zika Acutely Infected Patients: Potential Implications in Innate and Adaptive Immune Response Signaling Pathways - Carvalho-Silva, Ana Carolina; Da Silva Junior, Almir Ribeiro; Rigaud, Vagner Oliveira-Carvalho; Martins, Waleska Kerllen; Coelho, Verônica; Pfrimer, Irmtraut Araci Hoffmann; Kalil, Jorge; Fonseca, Simone Gonçalves; Cunha-Neto, Edecio; Ferreira, Ludmila Rodrigues Pinto (Frontiers in Genetics, 2022)
Zika virus (ZIKV) is an arbovirus mainly transmitted by mosquitos in the genus Aedes. The first cases of ZIKV infection in South America occurred in Brazil in 2015. The infection in humans causes diverse symptoms from asymptomatic to a syndrome-like dengue infection with fever, arthralgia, and myalgia. Furthermore, ZIKV infection during pregnancy is associated to fetal microcephaly and neurological disorders. The identification of host molecular mechanisms responsible for the modulation of different signaling pathways in response to ZIKV is the first step to finding potential biomarkers, therapeutic targets and understanding disease outcomes. In the last decade, it has been shown that microRNAs (miRNAs) are important post-transcriptional regulators involved in virtually all cellular processes. MiRNAs present in body fluids can not only serve as key biomarkers for diagnostics and prognosis of human disorders but also contribute to cellular signaling offering new insights into pathological mechanisms. Here, we describe for the first time ZIKV-induced changes in miRNAs plasma levels in patients during the acute and recovery phases of infection. We observed that during ZIKV acute infection, among the dysregulated miRNAs (DMs), the majority is with decreased levels when compared to convalescent and control patients. We used system biology tools to build and highlight biological interactions between miRNAs and their multiple direct and indirect target molecules. Among the 24 DMs identified in ZIKV+ patients, miR-146, miR-125a-5p, miR-30-5p and miR-142-3p were related to signaling pathways modulated during infection and immune response. The results presented here are an effort to open new vistas for the key roles of miRNAs during ZIKV infection.